Mechanisms of spatial and temporal regulation of actin dynamics - Roy, Ankit Animesh (Technische Universität Dortmund, 2024)
Actin subunits in filaments exhibit accelerated ATP hydrolysis compared to monomers. The subsequent slow phosphate (Pi) release results in an age-dependent distribution of ADP-Pi and ADP subunits within the filament. This stochastic process prevents newer regions from severing, as turnover occurs primarily in older sections rich in ADP subunits. However, the mechanism underlying Pi release from actin filament cores remains elusive. In the initial portion of this study, we present the mechanism responsible for Pi egress from actin filament cores. Our findings indicate that Pi can readily escape through a molecular backdoor in the terminal subunit which is largely occluded in the core of the filament. Utilizing molecular dynamics simulations, we identified potential egress pathways for the exit of Pi from filament cores. These escape pathways appeared to be obstructed by an intricate network of hydrogen bonding involving residues previously associated with disease-linked mutations. Lastly, our study demonstrates that disrupting this hydrogen-bonding network with actin mutants that confer an open-backdoor conformation results in increased Pi release in both bulk polymerization and single filament measurements. The Arp2/3 complex initiates lamellipodial protrusions and endocytic actin patches through nucleation of force-generating branched actin networks. The activity of the Arp2/3 complex is regulated by Nucleation Promoting Factors (NPFs), characterized by a conserved C-terminal domain that activates the Arp2/3 complex and diverse N-terminal domains that exert spatial and temporal control over the NPFs. While some NPFs are autoinhibited and require the release of intramolecular autoinhibition by GTPases and phosphatidylinositol lipids for activation, others exhibit unclear regulatory mechanisms. Importantly, all NPFs assemble branched actin networks exclusively from cellular membranes. In the second section of this study, we propose a novel density-dependent mechanism for the regulation of NPF activity. We demonstrate that NPFs recruited to the membrane can spawn a branched actin network from a pool of profilin-actin under physiological concentrations of Arp2/3 complex and capping protein, whereas NPFs in solution cannot. Moreover, the nucleation process shows a switch-like response to membrane-bound NPF density, with nucleation only occurring above a threshold density. The concentration of capping protein can further tune this density-dependent response of NPF activity. Our findings suggest that this density-dependent regulation operates on NPFs regardless of autoinhibition, thus superseding the traditional autoinhibition mechanism.
Keywords: Actin; Arp2/3 complex; NPF; 570; 540; Actin